Prevalence of overweight and obesity among women in two medical officer of health areas in Kalutara District - Deshani Herath; Anuradhani Kasturiratne (College of Community Physicians of Sri Lanka, 2023)
Introduction: Overweight and obesity are rising burdens in the w orld. Gender disparities in its prevalence are more evident in developing countries compared to developed countries. Objectives: To determine the prevalence of overweight and obesity  among 35-44-year-old women in Bandaragama and Horana Medical Officer of Health (MOH) areas Methods: This was a community-based descriptive cross-sectional  study conducted among 770 women aged 35-44 years residing in two MOH areas of Kalutara District for the l ast six months at the time of data collection. Overweight/obesity were assessed on the Asian cutoff values recommended by the WHO based on body mass index (BMI). The prevalence was estimated with 95% confidence interval (CI). Results: The prevalence of overweight in Bandaragama and Horana  MOH areas was 41.35% (95% CI: 37.9, 44.81) and 39.7% (95% CI: 36.3, 43.2), respectively, while the correspondi ng prevalence of obesity was 36.1% (95% CI: 32.8, 39.6) and 26.6% (95% CI: 16.4, 39.1). Conclusions & Recommendations: The prevalence of overweight /obesity among women aged 35-44 years was relatively high. Barriers to a healthy lifestyle, women's role in the  household and existing service gaps at primary healthcare level should be considered when preventive measures ar e introduced to reduce this burden.